Innovative technologies and barriers to their introduction in the field of tourism - Bespayeva, R.S.; Bugubayeva, R.O.; Tazhbayev, N.M.; Grelо M.F. (BUKETOV BUSINESS REVIEW, 2018)
In this paper, the necessity of developing innovative technologies in this sphere is substantiated. The development of innovative tourism will allow Kazakhstan to attract additional cash flows, establish strong international business ties and strengthen its position in the world arena. Also given are data on various factors hampering innovation in micro and medium-sized tourist firms. Innovative barriers are identified and explored within the innovation chain of regional tourism in its three main areas: organizational, environmental and innovation. The dynamic growth rate of the tourism industry is accompanied by exceptionally intense competition, which exerts strong pressure on tourism firms, forcing them to innovate in order to survive and grow. However, empirical studies and official statistics point to a rather modest level of innovation in the tourism sector, which largely explains the reasons for studying this trend. Modern research on the management of innovations in the field of tourism is not so well studied, and especially it concerns barriers to innovation in tourism.